2010
DOI: 10.1074/jbc.m110.132597
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 Mediates Ubiquitination and Degradation of Activating Transcription Factor 3

Abstract: Activating transcription factor 3 (ATF3) is a common stress sensor, and its rapid induction by cellular stresses (e.g. DNA damage) is crucial for cells to mount appropriate responses (e.g. activating the tumor suppressor p53) and maintain homeostasis. Although emerging evidence suggests that dysregulation of ATF3 contributes to occurrences of human diseases including cancer, the mechanism(s) by which ATF3 expression is regulated is largely unknown. Here, we demonstrate that mouse double minute 2 (MDM2) is a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…This mechanism is reminiscent of mechanisms utilized by many other AR repressors (60) and is in line with our previous findings that ATF3 can regulate cellular functions independent of its transcriptional activity (59,64). Whereas both the basic region and the ZIP domain of ATF3 can mediate proteinprotein interactions (25,41,59,64), we found that ATF3 directly bound AR through the ZIP domain. c-Jun, a bZIP protein capable of promoting prostate cancer cell growth (10), was previously shown to interact with AR (49), suggesting that the characteristic leucine residues in the ZIP domain might be responsible for AR binding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This mechanism is reminiscent of mechanisms utilized by many other AR repressors (60) and is in line with our previous findings that ATF3 can regulate cellular functions independent of its transcriptional activity (59,64). Whereas both the basic region and the ZIP domain of ATF3 can mediate proteinprotein interactions (25,41,59,64), we found that ATF3 directly bound AR through the ZIP domain. c-Jun, a bZIP protein capable of promoting prostate cancer cell growth (10), was previously shown to interact with AR (49), suggesting that the characteristic leucine residues in the ZIP domain might be responsible for AR binding.…”
Section: Discussionsupporting
confidence: 91%
“…To test whether ATF3 affected AR nuclear translocation, we coexpressed ATF3 (fused to mCherry) and AR (fused to green fluorescent protein [GFP]) in PC3 cells and examined cells under a fluorescence microscope. As expected (41,64), ATF3 was predominantly localized in the nucleus, and this subcellular localization pattern was not altered in the presence of androgen (Fig. 5A).…”
Section: Atf3 Interacts With Ar Via Its Zip Domainsupporting
confidence: 78%
“…Indeed, we previously showed that the binding of ATF3 to Tip60 can promote the removal of ubiquitin chains by the deubiquitinase USP7, thereby preventing Tip60 from proteasomal degradation (17). Because ATF3 can interact with MDM2 (38) and the latter E3 ubiquitin ligase was suggested to be involved in UV-induced Tip60 expression (16), there is also a possibility that ATF3 stabilized Tip60 by regulating MDM2 in the UV response. However, we did not find evidence that MDM2 could mediate the degradation of Tip60 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, deregulation of ATF3 is documented to contribute to tumorigenesis, presumably through lack of appropriate DNA damage responses. 98 Protein phosphatase 2A (PP2A) is a serine-threonine phosphatase involved in the DNA damage response. PP2A is a heterotrimer comprised of a catalytic C subunit, a structural A subunit, and several regulatory B subunits.…”
Section: Downstream Targets Of Mdm2mentioning
confidence: 99%